2022
DOI: 10.30762/jeels.v2i2.96
|View full text |Cite
|
Sign up to set email alerts
|

Training Of Learning Strategies in Writing Essay

Abstract: Writing essay is still considered difficult forEnglish students to master. The students are expected tobe able to express their ideas correctly without makingany chance of messages to be misinterpreted by thereaders; therefore, they have to know and use the bestor the most appropriate ways to write. The purpose ofwriting this article is to introduce learning strategiesand the possibility of training of learning strategies inwriting essay to English students. The first strategy isintegration of strategy with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, the students' writing strategies have also been considered as the other factor affecting significantly on their writing process and production. Furthermore, Winarto (2015) has also revealed that EFL students' writing strategies influence to their writing performance. Various types of writing strategies have been applied by practitioners in various realms: (1) direct strategies including memory, cognitive, and compensation strategies, and (2) indirect strategies including metacognitive, affective, and social strategies (O'Malley & Chamot, 1990;Oxford, 2003;Winarto, 2015).…”
Section: Writing Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the students' writing strategies have also been considered as the other factor affecting significantly on their writing process and production. Furthermore, Winarto (2015) has also revealed that EFL students' writing strategies influence to their writing performance. Various types of writing strategies have been applied by practitioners in various realms: (1) direct strategies including memory, cognitive, and compensation strategies, and (2) indirect strategies including metacognitive, affective, and social strategies (O'Malley & Chamot, 1990;Oxford, 2003;Winarto, 2015).…”
Section: Writing Difficultiesmentioning
confidence: 99%
“…Furthermore, Winarto (2015) has also revealed that EFL students' writing strategies influence to their writing performance. Various types of writing strategies have been applied by practitioners in various realms: (1) direct strategies including memory, cognitive, and compensation strategies, and (2) indirect strategies including metacognitive, affective, and social strategies (O'Malley & Chamot, 1990;Oxford, 2003;Winarto, 2015). Those strategies can be implemented successfully depending on each language learning context where they are integrated.…”
Section: Writing Difficultiesmentioning
confidence: 99%
“…Writing has been described as having three main activities: planning, formulating or composing, and revising, which in the traditional understanding of writing was understood as a linear procedure, a strict 'plan-outline-write' that had little to do with the complex activities that teachers observed in the composting process of their writers, as these were much more than building grammatically correct sentences (De La Paz, 2009;So & Lee, 2013;Winarto, 2015). As a direct consequence, writing demonstrates students' ability to master writing techniques, so students must be aware of writing as both a process and a product (Okasha & Hamdi, 2014).…”
Section: English Academic Writingmentioning
confidence: 99%
“…The insights gained from the findings can be used by educators to design effective teaching materials and methods, and by students to improve their essay writing skills. Based on the suitability of teachers, students, subjects, and situations, the model of training of learning strategies in essay writing should be applied and developed (Winarto, 2015).…”
Section: Relationship Between the Strategies Used And The Students' P...mentioning
confidence: 99%